Penerapan Algoritme Advanced Encryption Standard (AES-128) untuk Mengamankan File Rekam Medis Pasien - Tamin, Zulfiqar; Hendrik, Billy (Jurnal KomtekInfo, 2025)
In the era of Industry 4.0, which describes the current trend of digital transformation and advancements in information systems, data and information security is of paramount importance for today's internet users. Data breaches involving patient medical records are among the most damaging incidents, necessitating enhanced security measures. This is the background for the development of this application. The problem analysis conducted by the researchers focuses on data file security. One effective method to enhance the security of your data or files is through encryption, specifically using the AES-128 cryptographic algorithm. Given the critical need for information security today, this research aims to implement cryptography using the AES-128 algorithm for encrypting and decrypting data in file formats. This study is implemented in a Python-based application, enabling users to protect sensitive data files. The data is encrypted, and only those with the application and the encryption key can decrypt or access the files. Several tests on this application have successfully encrypted and decrypted patient medical records in PDF format. The purpose of this application is to provide enhanced security for confidential file contents, ensuring that unauthorized parties cannot access them. The application was tested by encrypting and decrypting files in PDF format, with encryption and decryption times measured in seconds. The conclusion drawn from the AES-128 file encryption and decryption is that the larger the file size, the longer the encryption and decryption processes take